PENGARUH KETENAGAKERJAAN, PENGELUARAN PEMERINTAH DAN INFRASTRUKTUR EKONOMI TERHADAP KESEJAHTERAAN MASYARAKAT DI INDONESIA - Siska Demi Putri; Ali Anis; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research  aims to determine (1) the effect of labor on social welfare in Indonesia, (2) the effect of goverment expenditure on social welfare in Indonesia, (3) the effect of road infrastruktur on social welfare in Indonesia, (4) the effect of labor, goverment expenditure, and road infrastruktur on social welfare in Indonesia. The method used in this study is Multiple Linear Regression. The research type is descriptive research while the data used is time series data from 1987-2016 obtained from documentation of Bank Indonesia, and BPS Indonesia. The results of this study indicate that (1) labor has a significant positive effect on social welfare in Indonesia (2) goverment expenditure has a significant positive effect on social welfare in Indonesia  (3) road infrastruktur has a significant positive effect on social welfare in Indonesia, (4) labor, goverment expenditure, and road infrastruktur has a significant positive effect on social welfare in Indonesia.